The NAC Transcription Factor ANAC087 Induces Aerial Rosette Development and Leaf Senescence in Arabidopsis - Vargas-Hernández, Brenda Yazmín; Núñez-Muñoz, Leandro; Calderón-Pérez, Berenice; Xoconostle-Cázares, Beatriz; Ruiz-Medrano, Roberto (Frontiers in Plant Science, 2022)
CmNACP1 mRNA has been shown to move long-distance through the phloem in Cucurbita maxima (pumpkin) and through a graft junction. While the phloem transport of several different mRNAs has been documented in other systems as well, its function remains, for most of these RNAs, largely unknown. To gain insight into the possible role of these RNAs, we searched for the closest homologs of CmNACP1 in Arabidopsis, a model plant much more amenable for analysis. A phylogenetic approach using the predicted NAC domain indicated that ANAC059, ANAC092, ANAC079, ANAC100, ANAC046 and ANAC087 form a single clade with CmNACP1. In the present work we analyzed the possible function of the ANAC087 gene with more detail. The promoter region of this gene directed expression in the vasculature, as well as in trichomes, stem, apexes, and developing flowers which supports the notion that ANAC087 and CmNACP1 are orthologs. Overexpression of the ANAC087 gene induced increased branching in inflorescence stem, as well as development of ectopic or aerial rosettes in T1 and T2 plants. Furthermore, overexpression of ANAC087 leads to accelerated leaf senescence in 44 days post-germination (dpg). Interestingly, a similar phenotype was observed in plants expressing the ANAC087 gene upstream region, also showing an increase in ANAC087 transcript levels. Finally, the results shown in the present work indicate a role for ANAC087 in leaf senescence as well as in rosette development.